Morphological Changes of Renal Corpuscles in Male Mongolian Gerbils at Different Ages - LI Meng; CHEN Bai'an; LU Jing (Shiyan dongwu yu bijiao yixue)
Objective By observing and comparing the changes in renal corpuscles at the largest longitudinal section in male Mongolian gerbils of different ages, this study preliminarily explored potential patterns of renal corpuscle changes, providing foundational data for the selection of male Mongolian gerbils for research on the pathogenic mechanisms and drug screening of nephropathy. Methods Kidney samples were collected from male Mongolian gerbils aged 12, 48, and 72 weeks. After making longitudinal cuts along the largest coronal plane in the middle, kidney tissue sections were prepared. Following HE staining, panoramic electronic tissue sections were scanned, and images of renal corpuscles at the largest longitudinal plane were captured using CaseViewer. The areas of renal corpuscles and their glomeruli and renal vesicles were measured. Statistical analysis was performed using IBM SPSS Statistics 27, and figures were created using GraphPad Prism 8. Results Compared with the 12-week group, both the area of renal corpuscle (P=0.029) and glomerulus (P=0.001) significantly increased in the 48-week group, while there was no significant change in the area of renal vesicle (P=0.478). The proportion of glomerular area within the renal corpuscle showed an increasing trend but the difference was not statistically significant (P=0.163). Compared to the 48-week group, the areas of renal corpuscle, glomerulus, and renal vesicle were all significantly larger in the 72-week group (P<0.001), but the proportion of glomerular area within renal corpuscle decreased significantly (P<0.001). Conclusion The renal corpuscles in male Mongolian gerbils continued to increase from 12 to 72 weeks of age. There might be a certain pattern in this process of enlargement, where the trends of glomerular and renal corpuscle enlargement were relatively consistent. However, the enlargement of renal vesicles appeared to lag behind that of the renal corpuscle. It was speculated that the enlargement of renal corpuscles was mainly caused by the passive enlargement of renal vesicles due to glomerular enlargement. The enlargement of renal corpuscles might be achieved through multiple cycles of "glomerular enlargement - triggering renal vesicle enlargement".